Formación permanente del profesorado: Dimensión social - Pérez González, Lourdes (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2024)
This article shows the necessity of the various professionals of education and culture to take a continuous coordinated training adapted to the interests marked out by today' society.